American animals [videorecording (DVD)] - Layton, Bart; Peters, Evan, 1987-; Dowd, Ann; Keoghan, Barry, 1992-; Jenner, Blake, 1992- (Lions Gate Entertainment, 2018)
Four young men mistake their lives for a movie and attempt one of the most audacious heists in U.S. history.